Writing Support for International Graduate Students: Enhancing Transition and Success - Sharma, Emily (Journal of International Students, 2020)
Writing Support for International Graduate Students: Enhancing Transition and Success by Shyam Sharma is a valuable addition to the Routledge Research in Writing Studies series. In actuality, this volume’s audience is far wider than its title suggests. It includes thoughtful, holistic discussions of the needs of international graduate students to inform practitioners at every institutional level. Researchers in many fields, including composition, second language acquisition, educational policy, and student affairs, will also benefit from the book’s thorough literature review. Sharma’s primary argument is that strong leadership is essential to address the challenges faced by international graduate students.